ANALYSIS OF THE EFFICIENCY LEVEL OF FISH AUCTION PLACES IN NORTH JAKARTA CITY - M. Beferly Argajuna Dede Arta Pratama; Indrianty Sudirman; Andi Nur Baumassepe (Scientia Integritas Utama, 2023)
Fish Auction Place can be interpreted as a place where the sellers and buyers is doing the transaction of fish through the auction process, in this case the process of selling the fish using bidding way in a public. North Jakarta City has 3 (three) active fish auction places which are TPI Muara Angke , TPI Muara Baru, and TPI Kalibaru. Efficiency is the ratio of output and input. DEA is a non parametric method that uses a linear programming model to calculate the ratio of output and input for all units that are compared. This study aims to identify infrastructure facilities, analyze the efficiency level and compare the efficiency of Fish Auction Locations in North Jakarta. The method used in this research is descriptive method. Sampling method used is purposive sampling. The method used to analyze the efficiency of TPI is the forth DEA banxia forontier analysis tool. There are two out of three TPI that have been efficient or can be said to have score of 100% efficiency that are TPI Muara Angke and TPI Muara Baru. As for Kalibaru TPI has not achieved efficient scores and obtained a score of 21.2% efficiency.